(untitled) (Cardiovascular Journal, 2019)
Background: The Chiari network is mobile, serpentine, filament-like structures occasionally seen in right atrium near the opening of inferior vena cava and coronary sinus. Sometimes it may cause diagnostic confusion with right atrial pathologies. Methods: This was a cross sectional study conducted from September 2017 to August 2018 in a private consultation center in Dhaka. All patients who underwent transthoracic echocardiography were included. Chiari network was diagnosed and any relevant clinical condition was recorded. Results: Out of 1832 echo studies, Chiari network was found in 90 subjects giving a prevalence of 4.91%. More than half (55.6%) had otherwise normal heart, 20% had ischaemic heart disease, 7.8% had cardiomyopathy, 6.7% congenital heart disease, while 3.3% had valvular heart disease. Conclusion: The Chiari network is often an incidental diagnosis, though it may not be so rare. Clinicians should be aware of it to avoid diagnostic dilemma and to overcome difficulties while performing cardiovascular interventions. Cardiovasc. j. 2019; 11(2): 93-97